ZigBee Healthcare Monitoring System for Ambient Assisted Living Environments - Buthelezi, Bongisizwe Erasmus; Mphahlele, Maredi; Deon Du Plessis, Deon; Maswikaneng, Solly; Mathonsi, Topside (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
Healthcare Monitoring Systems (HMSs) are promising to monitor patients in hospitals and elderly people living in Ambient Assisted Living environments using Wireless Sensor Networks. HMSs assist in monitoring chronic diseases such as Heart Attacks, High Blood Pressure and other cardiovascular diseases. Wearable and implanted devices are types of Body sensors that collect human health related data. Collected data is sent over Personal Area Networks (PANs). However, PANs are facing the challenge of increasing network traffic due to the increased number of IP-enabled devices connected in Healthcare Monitoring Systems to assist patients. ZigBee technology is an IEEE 802.15.4 standard designed to address network traffic issues in PANs. To route traffic, ZigBee network use ZigBee Tree Routing (ZTR) protocol. ZTR however suffers a challenge of network latency caused by end to end delay during packet forwarding. This paper is proposing a New Tree Routing Protocol (NTRP) for Healthcare Monitoring Systems to collect Heart Rate signals. NTRP uses Kruskal’s minimum spanning tree to find shortest routes on a ZigBee network which improves ZTR. Neighbor tables are implemented in NTRP instead of parent–child mechanism implemented in ZTR. To reduce end to end delay, NTRP groups’ nodes into clusters and the cluster heads use neighbor tables to forward heart rate data to the destination node. NS-2 simulation tool is used to evaluate NTRP performance.